Quinoline based receptor in fluorometric discrimination of carboxylic acids - Ghosh, Kumaresh; Adhikari, Suman; Chattopadhyay, Asoke P.; Chowdhury, Purnendu Roy (Beilstein Journal of Organic Chemistry, 2008)
Quinoline and naphthalene-based fluororeceptors 1 and 2 have been designed and synthesized for detection of hydroxy carboxylic acids in less polar solvents. The receptor 1 shows monomer emission quenching followed by excimer emission upon hydrogen bond-mediated complexation of carboxylic acids. The excimer emission distinguishes aromatic dicarboxylic acids from aliphatic dicarboxylic acids and even long chain aliphatic dicarboxylic acids from short chain aliphatic dicarboxylic acids. The receptor 1 is found to be selective for citric acid with a strong excimer emission in CHCl3. On the contrary, the receptor 2 exhibited less binding constant value and did not form any excimer upon complexation with the same acids under similar conditions. This established the role of quinoline ring nitrogen in binding with the acids.
Keywords: carboxylic acid recognition; excimer emission; naphthalene; quinoline